2023
DOI: 10.1101/2023.02.06.527297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The remarkable complexity of the brain microbiome in health and disease

Abstract: Microbes in human brain and their potential contribution to neurodegenerative conditions such as ‎Alzheimer's disease (AD) have long been debated. We recently developed a new method (the ‎electronic tree of life, eToL) based on small subunit ribosomal RNA (rRNA) probes, further ‎confirmed by large subunit rRNA analysis, to comprehensively address the spectrum of ‎microorganisms in control and AD brain. We report a remarkable diversity of brain microbes in ‎control brain. The most abundant are fungi, bacteria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…A recently reported development is the use of longer probes: the electronic Tree of Life (eToL) method uses a net of much longer (64-mer) probes, prefiltered against human sequences, to identify (by homology; non-exact matches are detected) all non-human rRNA sequences in a given dataset. The method may be less prone to false positives because it refilters matches against human sequences and is relatively insensitive to single-nucleotide changes [54,55], and is being explored as a potential diagnostic method on patient samples.…”
Section: (V) Rna-seq With K-mer or Etol Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently reported development is the use of longer probes: the electronic Tree of Life (eToL) method uses a net of much longer (64-mer) probes, prefiltered against human sequences, to identify (by homology; non-exact matches are detected) all non-human rRNA sequences in a given dataset. The method may be less prone to false positives because it refilters matches against human sequences and is relatively insensitive to single-nucleotide changes [54,55], and is being explored as a potential diagnostic method on patient samples.…”
Section: (V) Rna-seq With K-mer or Etol Methodsmentioning
confidence: 99%
“…Over recent decades multiple studies on post-mortem AD brain have reported that diverse pathogens are present, ranging from bacteria to fungi to viruses [45][46][47][48][49][50][51][52][53]. Archaea, Chloroplastida, and Holozoa have also been reported in brain [54,55]. There are multiple potential routes of entry to the brain (Figure 2).…”
Section: Microbes In Ad Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial titres increase with age in the hippocampus of both cognitively normal humans as well as in macaque (Appendix S7, Fig. S3), consistent with age‐related decline of the immune system, and there is growing evidence that AD brain contains elevated levels of diverse microbes versus control brain (MacDonald, 1986; Miklossy, 2011; Branton et al ., 2013; Itzhaki, 2014; Pisa et al ., 2015; Emery et al ., 2017; Balin et al ., 2018), as recently confirmed (Hu et al ., 2022, 2023).…”
Section: Ageing Immunosenescence and Age‐related Diseasementioning
confidence: 99%
“…Over recent decades multiple studies on post mortem AD brains have reported that diverse pathogens are present, ranging from bacteria to fungi to viruses 45–53 . Archaea, Chloroplastida, and Holozoa have also been reported in the brain 54,55 . There are multiple potential routes of entry to the brain (Figure 2).…”
Section: Introductionmentioning
confidence: 99%